1999
DOI: 10.1161/01.cir.100.14.1548
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Effects of 32 P Radioactive Stents in an Atherosclerotic Porcine Coronary Model

Abstract: Background-Experimental studies have demonstrated that 32 P radioactive stents reduce neointimal formation at 28 days in porcine iliac and coronary arteries. Our objective was to determine the long-term dose-response effects of 1.0-to 12.0-Ci 32 P radioactive stents in a porcine atherosclerotic coronary model. Methods and Results-Control (nϭ19) and 1.0-to 12.0-Ci 32 P radioactive (nϭ43) stents (total, nϭ62) were implanted in the coronary arteries of 31 miniature swine at 28 days after creation of a fibrocellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Carter et al 7 described increased neointima formation and adventitial fibrosis at 6 months using highactivity 32 P radioactive stents in atherosclerotic pig coronary arteries. A larger neointima and delayed neointimal healing 15 weeks after radioactive stent implantation in dog coronary arteries were also reported by Taylor et al 8 However, a sustained reduction of neointimal proliferation but incomplete vessel wall healing 1 year after the implantation of high-activity 32 P radioactive stents in rabbit iliac arteries was communicated by Farb et al 9 Compared with radioactive stents, long-term animal data on catheter-based intracoronary radiation are incomplete.…”
Section: See P 2388mentioning
confidence: 99%
“…Carter et al 7 described increased neointima formation and adventitial fibrosis at 6 months using highactivity 32 P radioactive stents in atherosclerotic pig coronary arteries. A larger neointima and delayed neointimal healing 15 weeks after radioactive stent implantation in dog coronary arteries were also reported by Taylor et al 8 However, a sustained reduction of neointimal proliferation but incomplete vessel wall healing 1 year after the implantation of high-activity 32 P radioactive stents in rabbit iliac arteries was communicated by Farb et al 9 Compared with radioactive stents, long-term animal data on catheter-based intracoronary radiation are incomplete.…”
Section: See P 2388mentioning
confidence: 99%
“…[23][24][25][26][27] Further, a recent report has shown that continuous low-dose rate irradiation delivered by radioactive stent promotes "atheromatous" neointimal formation. 28 Therefore, a question still remains to be elucidated: Does endovascular radiation have any influence on the progression of atherosclerosis, especially in the adjacent nontarget irradiated segments? Figure 3.…”
Section: Study Limitationsmentioning
confidence: 99%
“…9 -12 There is only anecdotal evidence of the substrate of this edge effect. 13 Possible explanations for this edge phenomenon are the stimulation of tissue proliferation 14,15 or excessive extracellular matrix 16,17 by low-dose irradiation, by mechanical injury, 18 -20 or by a combination of both. The latter has been described in clinical endovascular radiotherapy as geographic miss.…”
mentioning
confidence: 99%